Illness perceptions of people with chronic hip pain: A qualitative investigation - De Oliveira, Beatriz Ito Ramos; Bunzli, Samantha; Smith, Anne; O’Sullivan, Peter; Haebich, Samantha; Fick, Daniel; Khan, Riaz (2019)
Background: Chronic hip pain is one of the leading causes of global disability. It can lead to significant physical and functional impairments, sleep disturbances and psychological distress. The biomedical model of illness is insufficient to explain persistent hip pain as it fails to consider biopsychosocial components strongly associated to musculoskeletal pain and disability. In particular, negative illness perceptions can lead to emotional distress, and progressive pain and disability. In this context, the Common Sense Model links illness perceptions with behavioural and emotional responses to manage health threats. To date, in-depth illness perceptions of people with persistent hip pain have not been investigated. Purpose: The purpose of this study was to explore illness perceptions, coping strategies and care seeking history of patients experiencing chronic hip pain within the Common Sense Model. Methods: This was a cross-sectional qualitative study with a deductive framework analysis approach. It was conducted between 2016 and 2017 as the initial stage of a prospective intervention study for hip pain management. Patients with chronic hip pain were referred to this study by two orthopaedic surgeons from a private clinic in Perth, Western Australia. Sixteen patients (µ age = 51 [SD 10.7]) participated in face-to-face interviews following a semi-structured interview guide based on Leventhal's Common Sense Model. This included seven key categories of beliefs: interpretation, identity, cause, consequences, time line, controllability, and action and appraisal. The seven categories were applied onto the framework analysis comprised of six steps: familiarisation, application of the framework, indexing, charting, mapping and interpretation of the data. Results: Four key themes emerged: 1. Discrepancies between what patients believed to be the cause(s) of their hip pain and how health professionals explained their symptoms based on the biomedical model (e.g. patients believed their pain was the result of exercise-related injuries that could be treated whilst health professionals interpreted altered hip alignment and aging as the cause); 2. Illness perceptions informed by pathoanatomical explanations provided by health professionals negatively impacted emotional state and behavioural responses (e.g. patients reported that medical imaging revealed extensive structural hip damage, leading to fear, anxiety or frustration); 3. Differentiation between strategies to “fix the damage” to their hip and “control the symptoms” (e.g. patients described unsuccessful attempts to “fix their hip” through physiotherapy, stem cell injections, or tried to “control their symptoms” through activity-avoidance, acupuncture, cortisone injections; but many believed hip replacement was the only solution); and 4. The negative impact of hip pain on the ability to exercise and sleep and the consequences to their psychosocial health (e.g. patients exercised to maintain psychosocial health but this strategy was compromised by pain). Conclusion(s): People with chronic hip pain presenting for surgical consultation have illness perceptions that are heavily influenced by a pathoanatomical framework which negatively affects emotional and behavioural responses. Implications: The recognition of illness perceptions and their role in perpetuating disability, avoidance and distress is important for clinicians treating chronic hip pain. Clinicians can play an important role in minimising patients' disability and distress by positively modifying illness perceptions.